Developing point-of-care tools to inform decisions regarding prescription medication use in pregnancy - Animesh Kumar Paul; Sunil Vasu Kalmady; Russell Greiner; Padma Kaul (npj Women's Health)
Abstract Pregnant women are often excluded from randomized clinical trials due to safety concerns, yet the increasing prevalence of pre-existing conditions and pregnancy complications necessitates medication use. Observational cohort data can provide valuable insights to support clinical decision-making. We developed a web-based tool that presents population-level data on medication use and preterm birth risk. By integrating real-world evidence, this tool helps clinicians assess medication-related outcomes and improve maternal and neonatal health.